Frequency of Punctures in Patients with Dengue Infection - Suwanmajo, Chantaporn; Sawasdivorn, Siraporn (Journal of Health Science of Thailand, 1992)
Number of punctures received by patients with Dengue virus infection attending Pediatric Section of Mahasarakham Hospital during Oct 1, 1987 to Sep 30, 1988 were studied. These included the punctures for complete blood count (CBC), hematocrit (Hct), other laboratory tests, as well as intravenous medication. There were altogether 725 cases: 362 with final diagnosis of Dengue hemorrhagic fever (DHF), 215 with Dengue fever (DF), and 148 cases with high fever suspected of Dengue infection (ND). It was found that the mean frequency of punctures was 13.56 times (max 42 – min 1) for the DHF group, 6.09 times (max 22 – min 1) for the DF group, and 5.94 times (max 31 – min 1) for the ND group. The mean for DHF group was significantly much higher than the other two, espectially in frequency of punctures. Only for mean frequency of hematocrit punctures. The high number of punctures that the children have received clearly demonstrated how painful they were. Therefore we should limit the number of punctures by ordering the practice only when necessary.